Picture languages in automatic radiological palm interpretation - Tadeusiewicz, Ryszard (1947- ); Ogiela, Marek R. (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents a new technique for cognitive analysis and recognition of pathological wrist bone lesions. This method uses AI techniques and mathematical linguistics allowing us to automatically evaluate the structure of the said bones, based on palm radiological images. Possibilities of computer interpretation of selected images, based on the methodology of automatic medical image understanding, as introduced by the authors, were created owing to the introduction of an original relational description of individual palm bones.
Keywords: syntactic pattern recognition; image understanding; medical image analysis; computer-aided diagnosis; palm disease diagnostics